2012
DOI: 10.1111/j.1467-9361.2012.00666.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional Economic Disparity, Financial Disparity, and National Economic Growth: Evidence from China

Abstract: The dynamic relations among national economic growth, economic disparity, and financial disparity in China are examined. Specifically, the focus is on whether economic disparity or financial disparity affects national economic growth. As measures of economic and financial disparity across regions and provinces, the Williamson coefficient of disparity is employed using both regional data (eastern, central, and western) and provincial data (from 31 provinces). Overall, it is found that both provincial financial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Additionally, the control variable Location is significantly positive at the statistical level of 5%, suggesting that there are regional differences in the quality and level of environmental disclosure for Chinese listed polluting firms; Firms located in eastern coastal regions of China have higher EID than those located in other regions, and are more willing to disclose environmental information about energy consumption, environmental facilities operation and emissions. This regional disparity is consistent with the imbalanced regional economic development in China, in which eastern coastal regions and modern industries have been given priority since the beginning of China's economic reform (Lee et al, 2012).…”
Section: Eid and Financing Needssupporting
confidence: 63%
See 1 more Smart Citation
“…Additionally, the control variable Location is significantly positive at the statistical level of 5%, suggesting that there are regional differences in the quality and level of environmental disclosure for Chinese listed polluting firms; Firms located in eastern coastal regions of China have higher EID than those located in other regions, and are more willing to disclose environmental information about energy consumption, environmental facilities operation and emissions. This regional disparity is consistent with the imbalanced regional economic development in China, in which eastern coastal regions and modern industries have been given priority since the beginning of China's economic reform (Lee et al, 2012).…”
Section: Eid and Financing Needssupporting
confidence: 63%
“…Third, the use of a scale allows us to exclude irrelevant or redundant information and which is claimed to be more objective than techniques such as relying on word counts (Cormier & Magnan, 2007). 3 In the beginning of China's economic reform, priority has been given to eastern coastal regions and modern industries towards economic development, which results in great regional disparity (Laffont & Qian, 1999;Lee, Peng, Li, & He, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Although China is the world's second largest economy, the situation of uneven development still exists. It is found that economic disparity exists between regions and provinces in China, and the disparity has a negative impact on economic growth (Lee et al, 2012) [32]. Many low-income people in rural areas are excluded from the growth of the economy while cities and developed areas tend to gather more resources and receive preferential treatment from the financial system.…”
Section: Current Situation Of Financial Inclusion In Chinamentioning
confidence: 99%
“…Because in many laboratories around the world, FISH is the first line test and IHC is the reflex test. However, in addition to the well-known socioeconomic disparities within China [ 25 ], substantial regional disparities exist, generally leading to insufficient financial resources and health-care staff in undeveloped regions. IHC is still the first step in HER2 detection.…”
Section: Introductionmentioning
confidence: 99%